Efficacy of guided self-change for smoking cessation in chronic obstructive pulmonary disease patients: A randomized controlled clinical trial - Mehran Zarghami; Fatemeh Taghizadeh; Ali Sharifpour; Abbas Alipour (Tobacco Induced Diseases, 2019)
Introduction The aim of this study was to examine the efficacy of guided selfchange (GSC), nicotine replacement therapy (NRT), and their combination, on smoking cessation among patients with COPD.